Synchrotron radiation based studies of complex molecules on surfaces - Handrup, Karsten (2014)
In this thesis two single molecule magnets based on the dodecamanganese (III, IV) cluster, with either benzoate or terphenyl-4-carboxylate ligands have been studied on the Au(111) and rutile TiO2(110) surfaces. We have used in situ electrospray deposition to produce a series of surface coverages from a fraction of a monolayer to multilayer films in both cases. X-ray absorption spectroscopy measured at the Mn L-edge (Mn 2p) has been used to study the effect of adsorption on the oxidation states of the manganese atoms in the core. In the case of the enzoate-functionalized complex, reduction of the manganese metal centres is observed due to the interaction of the manganese core with the underlying surface. In the case of terphenyl-4 carboxylate, the presence of this much larger ligand prevents the magnetic core from interacting with either the gold or the titanium dioxide surfaces and the characteristic Mn3+ and Mn4+ oxidation states necessary for magnetic behaviour are preserved.